Bending the arc of the staples trap: Negotiating rural resource revenues in an age of policy incoherence. (April 2019) - Markey, Sean; Halseth, Greg; Ryser, Laura; Argent, Neil; Boron, Jonathan
Abstract: Different political and economic contexts are shaping how resource royalties/revenues are collected and distributed back into the regions from which the resources are extracted. Within the context of peripheral resource community and regional development lifecycles, and drawing from staples theory and evolutionary economic geography, we look at the changing power relationships between the Province of British Columbia and the communities of the Peace River region in Canada through two sets of revenue sharing negotiations: the Fair Share Agreement and the Peace River Agreement. In the former case, the lack of an explicit provincial policy regime around the redistribution of state royalties and taxes created space for the region's communities to seize the agenda and maximize benefits from their negotiations with the Province. These communities achieved this through extensive research, preparation, and a coordinated negotiating plan. Following the success of this agreement, however, the region was unable to remain cohesive. In the latter case, the Province recaptured the agenda and set the framework for negotiating a new agreement. The result was a fragmentation of regional coherence and collaboration, and a recapturing of 'power' by the provincial government. As resource-dependent places and regions struggle along the historically defined pathway or 'arc' of staples dependence, the communities of the Peace River region have worked to initiate a break from that pathway or to 'bend the arc' of the staples trap. Coincident with such local initiatives, this research also highlights how senior governments, themselves dependent upon natural resource revenues, have worked to limit opportunities for resource-dependent places to achieve this change. Highlights: Rural regions struggle to diverge from an historically defined "arc" of staples dependence. Royalty regimes offer potential revenue return to rural resource regions. Lack of explicit policy regime creates opportunities for regional organization. Pathway tension exists between rural regions and senior governments.